The Monstrous Other in Contemporary Gothic: Ben As a Figure of Abjection in Doris Lessing's Fiction - HADAOUİ, HASSAN (İstanbul Kültür Üniversitesi, 2025)
This thesis examines the portrayal of Otherness in Doris Lessing's The Fifth Child and Ben, in the World; it argues that the Gothic's primary concern is no longer the fear of the monstrous Other, but instead a profound danger of society's failure to absorb and accept differences. Using the theoretical frameworks of Julia Kristeva's concept of abjection, Bracha L. Ettinger's matrixial Borderspace, and John Bowlby's attachment theory to explore how Lessing's narratives introduce a new perspective of the Gothic fiction by locating monstrosity within the domestic sphere and framing the othered figure not as a threat but as a subject who seeks recognition, care and emotional connections. Ben's characters in the two novels challenge traditional views of normalcy and humanity, as well as the families and social roles that construct otherness. This study places the novels in an evolving Gothic genre. Lessing's works further demonstrate Otherness in contemporary Gothic fiction through a social and psychological framework, establishing that the monster is not only an external figure but also a fragmented internal condition resulting from social constructions. The horror is not arising from the presence of the Other, but of the society itself, its cultural norms and social structures that stigmatise and refuse to accept and acknowledge differences.
Keywords: Otherness; Gothic Fiction; Abjection; Julia Kristeva; Bracha Ettinger; Matrixial Borderspace; Attachment Theory; Domestic Gothic; Subjectivity; Monstrosity; Alienation; Doris Lessing